Integrative analysis of TRPV family to prognosis and immune infiltration in renal clear cell carcinoma. Issue 1 (31st December 2022) - Gong, Zixuan; Xie, Jiaheng; Chen, Liang; Tang, Qikai; Hu, Yiming; Xu, Aiming; Wang, Zengjun
ABSTRACT: The transient receptor potential vanilloid (TRPV) family has been preliminarily discovered to play an important role in various cancers, including clear cell renal cell carcinoma (ccRCC), which is closely associated with immune infiltration. However, the expression and prognosis of TRPV family and tumor-infiltrating immune cells in ccRCC are obscure. This study aimed to explore the prognostic and therapeutic value of the TRPV family expression in ccRCC from the perspective of bioinformatics. We analyzed the transcriptome and clinical data of kidney renal clear cell carcinoma (KIRC) from The Cancer Genome Atlas (TCGA) database. A clustering analysis and immune infiltration analysis were conducted to investigate the influence of the TRPV family genes on ccRCC. Our study found that the TRPV family is an excellent prognostic stratification for ccRCC. Among them, TRPV3 is the most significant prognostic marker of ccRCC. In addition, we performed a drug sensitivity analysis to identify the drugs with the strongest association with TRPV3. As a result, the TRPV family, particularly TRPV3, can act as a prognostic biomarker in ccRCC to determine prognosis and levels of immune infiltration.